Propagation of elastic waves in adhesive contacts: experiment and numerical model - Lyashenko, Iakov A.; Filippov, Aleksander E.; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2024)
The entry and propagation of pores inside an adhesive interface between an elastomer and a rigid sphere were studied experimentally and simulated numerically. It was shown that mutually interacting events involving attachment–detachment of different segments of the elastomer to the indenter resulted in non-trivial patterns of spatially distributed contacts between them, which were additionally influenced by air penetration of the pores.